Transcranial Direct Current Stimulation (tDCS) in a Patient with PRES and Bipolar Depression - Palm, U.; Padberg, F.; Remi, J. (Fortschritte der Neurologie · Psychiatrie, 2015)
Transcranial direct current stimulation (tDCS) is a non-invasive tool for brain stimulation and has proven efficacy in depressive disorders. Here, we report the case of a patient with recurrent bipolar depressive disorder and neurologic complications due to posterior reversible encephalopathy syndrome (PRES) due to parathyroid adenoma. During a long-term hospital stay, multiple drug regimens did not resolve depressive symptoms. Finally, an add-on therapy with tDCS brought improvement of symptoms. This case highlights the feasibility of tDCS in treatment-resistant depression and concomitant neurologic disorder.
Keywords: parathyroid adenoma; status epilepticus; Posterior Reversible Encephalopathy Syndrome